Influence of contracting conditions on absenteeism - Torrano Montalvo, Fermín; Fernández-Suárez, Iván; Botey, María (Anales de Psicología / Annals of Psychology, 2020)
The purpose of this research is to analyze the relationship between hiring conditions and work absenteeism in a sample of 5.524 workers in order to identify which segments (by type of contract and workday, time hired, seniority in the company and sick leaves occurred in the last three years) are more related to the possibility of suffering a disease process in 2017. Descriptive analyzes, the chi-square test for contingency tables with two independent samples, and the decision trees based on the CHAID algorithm (Chi-squared Automatic Interaction Detection) were carried out to detect the most important variables in the identification of profiles with a greater probability of suffering a temporary disability. The results show the existence of differences between the variables studied. The hiring modality is considered an important risk factor for work absenteeism.